Application value and challenge of traditional Chinese medicine carried by ZIF‐8 in the therapy of ischemic stroke. Issue 4 (11th December 2021) - Zhu, Xiao‐Xi; Guo, Dong‐Fen; Chen, Ming; An, Xiao‐Qiong; Wang, Bi; Yu, Wen‐Feng
Abstract: Stroke is a group of major diseases that cause death or disability in adults, with high incidence and lack of available therapeutic strategies. Although traditional Chinese medicine (TCM) has continuously achieved good effects in the therapy of stroke while there is still not convincing due to the limitation of blood–brain permeability, as well as the individual differences in usage and dosage. With the improvement of nanotechnology, TCM nanopreparation has gradually become a research hotspot in various fields due to its advantages in permeating the blood–brain barrier, targeting delivery, enhancing sustained‐release drug delivery, changing the distribution in the body, and improving bioavailability. Zeolitic imidazolate framework‐8 (ZIF‐8) is an ideal nano‐drug delivery system for adsorption, catalysis, and drug loading, which is a biocompatible metal–organic framework framed by 2‐methylimidazole and zinc ions. At present, ZIF‐8 was wildly used in the treatment of ischemic stroke. However, challenges remain persists for its clinical application, such as preparation technology, detection technology in vivo, targeting specificity, safety and stability, and so forth. Therefore, more efforts need to overcome the above problems to develop the application of TCM nanopreparations in the therapy of ischemia/reperfusion in the future. Abstract : Research progress of the application of traditional Chinese medicine (TCM), TCM nanopreparation, and zeolitic imidazolate framework‐8 (ZIF‐8) nano‐drug delivery system in the treatment of ischemic stroke were reviewed in this article to explore the clinical application value and future challenges of ZIF‐8 as a nano‐drug delivery system in the treatment of nerve injury after ischemic stroke.